Beliefs about Foreign Language Learning at University Level - Gómez Paniagua, Juan Fernando (Íkala, Revista de Lenguaje y Cultura, 2017)
The beliefs of the students from Tecnológico de Antioquia (TdeA) were analyzed in this study, with regard to learning English as a foreign language. The aim of the current research was to identify those beliefs in order to improve the proposed curriculum for the language department of the institution. The representative sample of this study was comprised of 237 English students, ranging from levels 1-6 (161 women and 77 men). This number was determined by a matrix of sample sizes. A descriptive cross-sectional design was selected to conduct this research; data was collected through BALLI instrument (Beliefs About Language Learning Inventory), which was proposed by Horwitz (1987). The data were then analyzed using descriptive statistics. The results allowed to establish that most of the participants of this study had a strong instrumental and integrative motivation towards learning English. Similarly, it was found that some beliefs related to The Nature of Language Learning and Learning Strategies represent major hindrances. In conclusion, the participants hold English learning misconceptions that create barriers for them to achieve a successful communicative performance.